In vitro and in vivo characterization of designed immunogens derived from the CD‐helix of the stem of influenza hemagglutinin. Issue 10 (23rd July 2013) - Mallajosyula, V. Vamsee Aditya; Citron, Michael; Lu, Xianghan; Meulen, Jan ter; Varadarajan, Raghavan; Liang, Xiaoping
ABSTRACT: The conserved "stem" domain of influenza virus hemagglutinin (HA) is a target for broadly neutralizing antibodies and a potential vaccine antigen for induction of hetero‐subtypic protection. The epitope of 12D1, a previously reported bnAb neutralizing several H3 subtype influenza strains, was putatively mapped to residues 76–106 of the CD‐helix, also referred to as long alpha helix (LAH) of the HA stem. A peptide derivative consisting of wt‐LAH residues 76–130 conjugated to keyhole limpet hemocyanin was previously shown to confer robust protection in mice against challenge with influenza strains of subtypes H3, H1, and H5 which motivated the present study. We report the design of multiple peptide derivatives of LAH with or without heterologous trimerization sequences and show that several of these are better folded than wt‐LAH. However, in contrast to the previous study immunization of mice with wt‐LAH resulted in negligible protection against a lethal homologous virus challenge, while some of the newly designed immunogens could confer weak protection. Combined with structural analysis of HA, our data suggest that in addition to LAH, other regions of HA are likely to significantly contribute to the epitope for 12D1 and will be required to elicit robust protection. In addition, a dynamic, flexible conformation of isolated LAH peptide may be required for eliciting a functional anti‐viral response. Proteins 2013; 81:1759–1775. © 2013 Wiley Periodicals, Inc.